Challenges and opportunities of HIV positive adolescents in Zvishavane Urban. - Sesemani, Ngonidzashe (Midlands State University, 2017)
The Human Immunodeficiency Virus and Acquired Immuno Deficiency Syndrome commonly known as HIV and AIDS have had negative consequences towards the well-being of young people in particular HIV positive Adolescents. In a country with high prevalence rate in Southern Africa, the number of adolescents born and living with HIV and AIDS is steadily increasing. As reported by the National AIDS Council (2011) there are more than 150 000 children born and living with HIV and AIDS who are below the age of 15 years. In the preceding years, this group of the population has been receiving little or no attention at all from the duty bearers. The study analysed the challenges and opportunities of HIV positive adolescents in Zvishavane Urban. The objectives of the study were to identify the challenges of HIV positive adolescents, to examine the role of Government and NGOs in promoting the well-being of HIV positive adolescents and also to explore opportunities available for HIV positive adolescents. The study mixed quantitative and qualitative research methods in order to mine adequate data for the study. Data collection included key informant interviews, focus group discussions and a questionnaire. A sample of 35 HIV positive Adolescents age between 10 and 19 years of age were selected through simple random sampling. The study revealed that HIV positive adolescents continue to face challenges which range from individual, family and community level and these were perpetuated at home, school, church and in the community as a whole. The study revealed that these adolescents faced problems which include stigma and discrimination, disclosure of HIV status, limited or lack of knowledge and skills on HIV and SRH, unfriendly health delivery systems and poor adherence to antiretroviral treatment. NGOs in particular Bethany Project were found to be working tirelessly in addressing the challenges of HIV positive Adolescents with support from Government line Ministries such as the Ministry of Health and Child Care. Opportunities for HIV positive Adolescents were explored in this study and were identified as the existence of community based structures established by the Government and NGOs, availability of youth friendly centres and the existence of policies that support programming for HIV positive Adolescents. The study concludes that despite the efforts being made by the Government and NGOs, the well-being of HIV positive adolescents is still being hampered. The study informs interventions that promote healthy coping and better quality of service delivery for adolescents that are struggling with the complexities of living with HIV and AIDS.